2015
DOI: 10.1097/inf.0000000000000843
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Infection Because of Pandoraea sputorum in a Young Cystic Fibrosis Patient Resistant to Antimicrobial Treatment

Abstract: We report the case of a 13-year-old boy with cystic fibrosis with a pulmonary exacerbation concomitant to the first isolation of Pandoraea sputorum. The imipenem and trimethoprim-sulfamethoxazole treatments failed, with persistence of the bacteria, bronchial congestion and a decline in lung function. Pandoraea sp. is rarely isolated, with only 10 cases reported in France in 2011.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 7 publications
2
18
0
Order By: Relevance
“…These bacteria have been occasionally recovered from the lung transplant and/or respiratory tract of CF patients, as well as from blood cultures in non-CF patients and environmental samples [ 2 , 4 , 8 , 19 ]. In our review of the bibliography, we found few cases of CF patients chronically colonized with P. sputorum : one case from Australia [ 8 ], two cases from Spain [ 10 , 11 ], and one case from France [ 5 ]. Interestingly, in our CF patient, S. aureus and P. aeruginosa were eventually isolated from respiratory tract cultures together with P. sputorum .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These bacteria have been occasionally recovered from the lung transplant and/or respiratory tract of CF patients, as well as from blood cultures in non-CF patients and environmental samples [ 2 , 4 , 8 , 19 ]. In our review of the bibliography, we found few cases of CF patients chronically colonized with P. sputorum : one case from Australia [ 8 ], two cases from Spain [ 10 , 11 ], and one case from France [ 5 ]. Interestingly, in our CF patient, S. aureus and P. aeruginosa were eventually isolated from respiratory tract cultures together with P. sputorum .…”
Section: Discussionmentioning
confidence: 99%
“…Some of these species have been associated with poor outcomes in CF, and the role that others may play in disease progression remains uncertain [ 2 ]. Bacteria from the Pandoraea genus ( P. pulmonicula , P. pnomenusa , P. apista , P. norimbergensis and P. sputorum ) are NFGNB that are being considered as emerging multi-drug resistant pathogens in the context of CF [ 4 , 5 ]. As they are still poorly known, particularly in terms of mechanisms of natural or acquired resistance and of their impact on lung function and the prognosis of the disease [ 5 ], more information is needed it to evaluate their pathogenic role.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…After first colonization, Pandoraea spp. were able to chronically colonize the CF respiratory tract (CFRT) ( Fernández-Olmos et al, 2012 ; Kokcha et al, 2013 ; Pugès et al, 2015 ; Martina et al, 2017 ), were transmissible between patients ( Jørgensen et al, 2003 ; Degand et al, 2015 ) and can produce severe lung diseases and bacteremia ( Pimentel and MacLeod, 2008 ; Kokcha et al, 2013 ). The pathogenicity appears mainly supported by a pro-inflammatory response induction significantly greater than with Pseudomonas aeruginosa ( Caraher et al, 2008 ; Costello et al, 2014 ) and the treatment may be complicated by multidrug resistance conferred by carbapenem-hydrolyzing oxacillinases ( Caraher et al, 2008 ).…”
Section: Introductionmentioning
confidence: 99%